ASSESSMENT OF CAROTID ARTERY INTIMA MEDIA THICKNESS IN HYPERTENSIVE PATIENTS COMPARED WITH NORMOTENSIVES BY B-MODE ULTRASONOGRAPHY - Siddiqui, Tariq Saeed; Falak Nigar; Aisha Asim; Irfan-Ul-Haq; Bushra Rehman (Journal of Ayub Medical College Abbottabad, 2024)
Background: Cardiovascular disease is the leading cause of mortality and morbidity worldwide. Common carotid artery intima media thickness has recently generated considerable interest as a marker of atherosclerosis and in the prediction of clinical coronary events and coronary artery disease. Ultrasonography is a non-invasive technique of measuring carotid artery intima media thickness. This study was carried out at Military Hospital Rawalpindi during 6 months from 24th May to 24th Nov 2007 to compare the common carotid artery intima media thickness in hypertensive patients with normotensives.